"Governtrepreneurism" for good governance: The case of Aadhaar and the India Stack. Issue 2 (4th September 2019) - Dattani, Kavita
Abstract : In many of the ex‐colonies of European empires, biometric technology systems are being built under an ethos of welfare and financial service delivery. One case in this broader trend of postcolonial governance is India's Aadhaar and India Stack. This paper uses this case to explore how the in‐sourcing of technology into means of governing, behind a front of participatory "good governance, " is contributing to the historical trajectory of citizenship regimes in India. Through claims of reducing financial "leakages, " Aadhaar, a biometric identification database consisting of fingerprint, iris scan, and photograph, has become compulsory for accessing welfare in India. The Indian government makes a case for Aadhaar using a propaganda discourse of its success, based on weak evidence. The India Stack, a set of cloud‐based application programming interfaces (APIs) built on top of the Aadhaar database, offers a digital infrastructure for private companies to verify identities using Aadhaar data and to offer other "services" including "financial services." The ability to access data, paired with a "revolving door" of individuals between state and corporations, points to an ulterior goal of both Aadhaar and the India Stack: creating winners in the corporate and financial technology sectors. The Indian corporate‐state run through a "governtrepreneurism" uses Aadhaar and the India Stack as new digital technologies of governmentality to transform populations into subjects or customers. Abstract : This paper uses the case of Aadhaar, a biometric identification database consisting of fingerprint, iris scan, and photograph, and the India Stack, a set of cloud‐based application programming interfaces (APIs) built on top of the Aadhaar database, to explore how the in‐sourcing of technology into means of governing is contributing to the historical trajectory of citizenship regimes in India. It argues that Aadhaar and the India Stack manifest as new technologies of governmentality, pushing populations further into a status of subjects or customers of the Indian state.